Multimedia of Number Recognition for Early Childhood Using Image Object - Simarmata, Janner S; Limbong, Tonni; Tambunan, ARS; Purnama Simanjuntak, Mariati; Limbong, Riswan; Purnomo, Agung; Devi Kumalasari, Riesta; Anam, Fatkul; Khoifulloh, K; Nisa, Khairun; Aryni, Yen; Nirmala Purba, Oktaviana; et al. (International Journal of Engineering and Technology, 2018)
Many children are currently challenging to comprehend the mathematics learning, especially the counting. The children assumed that mathematics is a disliked subject, while most of the aspects in the daily life require the ability to count. The primary education about the numbers is still lacking. In early childhood, a math learning activity should be in a fun atmosphere in learning. To know numbers need to be presented creatively by using media such as multimedia-based computers so as not to get bored for the students. The application of number recognition for early childhood is equipped with sound to assist the students in pronouncing the numbers. By using the computer, the students can recognize the number 1 to 10 increased by about 37%, 39% of the students can write the numbers, and 15% of them can say the numbers.Â